Laplace-Adomian Decomposition method for solving fractional-order mathematical model of Monkeypox transmission dynamics - Agbata*, B.C.; Obeng-Denteh†, W.; Agbebaku‡§, D.F.; Shior**, M.M.; Yahaya††, D.J.; Danjuma‡‡, A.Y. (International Journal of Mathematical Analysis and Modelling, 2025)
In this study, we developed a model to understand and predict the spread of Monkeypox among humans and rodents, both of which are important in the disease’s transmission. Our model categorized the human population into six groups: susceptible individuals who have not been exposed, exposed individuals who have encountered the virus, infected individuals, quarantined individuals, those receiving treatment, and those who have recovered. For rodents, we considered three groups: susceptible, exposed, and infected animals, as they also play a key role in spreading Monkeypox. To explore how different control measures could impact the spread of the disease, we used a mathematical approach known as the Laplace Adomian Decomposition Method (LADM) to get an approximate solution to the model. This allows us to estimate the outcomes of various strategies in managing the disease. Our findings shed light on how actions like quarantining, treating infected individuals, and reducing the number of susceptible rodents can work together to slow or stop the spread of Monkeypox. This model gives public health officials a clearer picture of where to focus efforts to prevent outbreaks and protect communities.